A high-strength and toughness titanium alloy and heat treatment method thereof
By adding specific elements to high-strength tough titanium alloys and using step-by-step heating heat treatment methods, the sheet structure and refine the α phase are solved, and the shortcomings of existing titanium alloy materials in terms of strength, plasticity and toughness are achieved, and a higher Comprehensive performance.
Patent Information
- Application Number
- CN202411613360.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing high-strength and tough titanium alloy materials have not yet achieved higher comprehensive strength, plasticity and toughness when meeting the performance requirements of aviation aircraft.
High-strength tough titanium alloys with specific components, including Al 5.8%~6.2%, Mo 3.8%~4.2%, V 6.8%~7.2%, Nb 1.5%~2.5%, Fe 0.8%~1.5% and other elements, and pass the ladder The heat treatment method of heating and multiple insulation forms the sheet structure and refines the alpha phase, thereby improving the strength, plasticity and toughness of the material.
The tensile strength of high-strength tough titanium alloy is greater than 1200 MPa, elongation greater than 8%, and fracture toughness greater than 70 MPa·m1/2, which significantly improves the overall performance of the material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material science and technology, and in particular relates to a high-strength and toughness titanium alloy and a heat treatment method thereof. Background Art
[0002] At present, the most mature and widely used high-strength and toughness titanium alloys at home and abroad are TC18 and TB6 titanium alloys. The former is also called BT22 titanium alloy, with a strength level of 1080 MPa, an elongation of not less than 6%, and a fracture toughness of 60 MP·m 1 / 2 The latter is also called Ti-1023 titanium alloy, with a strength level of 1100 MPa, an elongation of not less than 6%, and a fracture toughness of 60 MP·m 1 / 2 . After decades of development, in order to meet the performance requirements of new aviation vehicles, both China and foreign countries are committed to developing new high-strength and toughness titanium alloy materials. At present, the most influential and representative of the latest research on high-strength and toughness titanium alloys are Ti-55531 and Ti-5553, which have been used in Airbus and Boeing respectively. Their strength remains at the 1100 MPa level, the elongation is not less than 6%, and the fracture toughness is increased to 65 MP·m 1 / 2 and 70 MP·m 1 / 2 It can be seen that improving the comprehensive performance of strength-plasticity-toughness is the eternal goal pursued by titanium alloys.
[0003] With the further improvement of the performance level, weight reduction target and design service life of the new generation of aircraft, the strength requirement of titanium alloy materials has exceeded 1100 MPa, and the plasticity and toughness are also pursued to be higher. At present, the development of high-strength and toughness titanium alloy materials and processes still requires a new type of high-strength and toughness titanium alloy with excellent strength-plasticity-toughness matching suitable for production. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a high-strength and toughness titanium alloy and a heat treatment method thereof.
[0005] The invention provides a high-strength and toughness titanium alloy, the components of which, by mass, include: Al 5.8%-6.2%; Mo 3.8%-4.2%; V 6.8%-7.2%; Nb 1.5%-2.5%; Fe 0.8%-1.5%; C≤0.05%; O≤0.13%; N≤0.05%; H≤0.015%; and Ti balance.
[0006] The present invention also provides a heat treatment method for a high-strength and toughness titanium alloy, comprising the following steps:
[0007] The titanium alloy forging is heated stepwise to the phase transition temperature + (10-30)°C for the first heat preservation, then cooled to 670-700°C for the second heat preservation, then transferred to an environment of 400-450°C, heated to 520-610°C for the third heat preservation, and a high-strength and toughness titanium alloy is obtained;
[0008] The composition of the titanium alloy forging includes, by mass, Al 5.8%-6.2%, Mo 3.8%-4.2%, V 6.8%-7.2%, Nb 1.5%-2.5%, Fe 0.8%-1.5%, C≤0.05%, O≤0.13%, N≤0.05%, H≤0.015%, and Ti balance.
[0009] Preferably, the staged heating includes first stage heating, second stage heating and third stage heating; the first stage heating is to 450°C~550°C; the first stage heating is followed by keeping warm for 10~40 min; the second stage heating is to 800°C~830°C; the second stage heating is followed by keeping warm for 10~40 min; the third stage heating is to phase change temperature + (10~30)°C.
[0010] Preferably, the staged heating includes first stage heating, second stage heating and third stage heating; the first stage heating is to 480°C~520°C; the first stage heating is followed by keeping warm for 20~40 min; the second stage heating is to 800°C~820°C; the second stage heating is followed by keeping warm for 20~40 min; the third stage heating is to phase change temperature + (10~30)°C.
[0011] Preferably, the staged heating includes first stage heating, second stage heating and third stage heating; the first stage is heated to 500°C; the first stage is heated and kept warm for 30 min; the second stage is heated to 810°C; the second stage is heated and kept warm for 30 min; the third stage is heated to phase change temperature + (10~30)°C.
[0012] Preferably, the first heat preservation is performed by stepwise heating to the phase change temperature + (10-15)°C.
[0013] Preferably, the first insulation time is 1 to 2 h; the second insulation time is 1 to 4 h; and the third insulation time is 3 to 5 h.
[0014] Preferably, the transfer time does not exceed 90 s.
[0015] Preferably, the titanium alloy forging is obtained by forging a titanium alloy ingot through a process combining repeated upsetting and drawing by a "high-low-high" method above and below the phase transformation point, wherein the deformation amount per fire at the phase transformation point is controlled between 45% and 55%, and the deformation amount per fire below the phase transformation point is controlled between 35% and 45%, and the forging is obtained through two-phase zone forging.
[0016] The titanium alloy provided by the present invention has a relatively high molybdenum equivalent of 12.12%, and about 2% of Nb and about 1% of Fe are added at the same time. The comprehensive performance ensures that the alloy has relatively high strength, plasticity and toughness.
[0017] The invention provides a heat treatment method for a high-strength and toughness titanium alloy. The composition of the titanium alloy forging includes, by mass, 5.8%-6.2% Al, 3.8%-4.2% Mo, 6.8%-7.2% V, 1.5%-2.5% Nb, 0.8%-1.5% Fe, C≤0.05%, O≤0.13%, N≤0.05%, H≤0.015%, and Ti remainder. The heat treatment comprises the following steps: heating the titanium alloy forging to a phase transition temperature+(10-30)°C in a stepwise manner for a first heat preservation, then cooling to 670°C-700°C for a second heat preservation, then transferring to an environment of 400°C-450°C, heating to 520°C-610°C for a third heat preservation, and obtaining a high-strength and toughness titanium alloy. The titanium alloy provided by the present invention has both a high aluminum equivalent and a high molybdenum equivalent. At the same time, Nb and Fe can significantly refine the grain size of the titanium alloy, and the addition of Nb can greatly improve the plasticity and toughness of the alloy, so that the alloy has higher strength, plasticity and toughness. At the same time, a specific strengthening and toughening heat treatment process is adopted according to the characteristics of the alloy. The titanium alloy forging is heated above the phase transformation point and then furnace-cooled to a certain temperature to obtain a lamellar structure of a certain thickness, and then quickly converted to a lower temperature. In the process, finer α phases are precipitated, and then more secondary α phases are precipitated through aging, so that the comprehensive performance of strength, plasticity and toughness of the titanium alloy is improved to a new level.
[0018] The experimental results show that the titanium alloy prepared by this process has a tensile strength greater than 1200 MPa, an elongation greater than 8%, and a fracture toughness greater than 70 MPa·m 1 / 2 . DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] The invention provides a high-strength and toughness titanium alloy, the components of which, by mass, include: Al 5.8%-6.2%; Mo 3.8%-4.2%; V 6.8%-7.2%; Nb 1.5%-2.5%; Fe 0.8%-1.5%; C≤0.05%; O≤0.13%; N≤0.05%; H≤0.015%; and Ti balance.
[0021] According to the present invention, the Al content may be specifically 5.9% to 6.2%, further specifically 5.9% to 6.11%, and further specifically 5.98% to 6.11%.
[0022] According to the present invention, the Mo content may be specifically 3.9% to 4.2%, further specifically 3.95% to 4.2%, and further specifically 3.99% to 4.18%.
[0023] According to the present invention, the V content may be specifically 6.85% to 7.2%, further specifically 6.85% to 7.15%, and further specifically 6.88% to 7.12%.
[0024] According to the present invention, the Nb content may be specifically 1.7% to 2.5%, further specifically 1.7% to 2.2%, further specifically 1.9% to 2.2%, and further specifically 1.98% to 2.1%.
[0025] According to the present invention, the Fe content may be specifically 0.8% to 1.3%, further specifically 0.9% to 1.25%, and further specifically 0.95% to 1.25%.
[0026] According to the present invention, the C content may be less than or equal to 0.04%, further less than or equal to 0.03%, further less than or equal to 0.02%, and further less than or equal to 0.01%.
[0027] According to the present invention, the content of O may be less than or equal to 0.12%, further less than or equal to 0.1%, and further less than or equal to 0.08%.
[0028] According to the present invention, the N content may be less than or equal to 0.03%, further less than or equal to 0.02%, further less than or equal to 0.01%, and further less than or equal to 0.008%.
[0029] According to the present invention, the H content may be specifically less than or equal to 0.012%, further specifically less than or equal to 0.01%, further less than or equal to 0.008%, further less than or equal to 0.005%.
[0030] According to the present invention, the tensile strength of the high-strength and toughness titanium alloy is preferably greater than 1200 MPa, more preferably 1210-1250 MPa, more preferably 1220-1250 MPa, and most preferably 1225-1240 MPa; the elongation of the high-strength and toughness titanium alloy is preferably greater than 8%, more preferably 9%-15%, more preferably 10%-15%, and more preferably 12%-15%; the fracture toughness of the high-strength and toughness titanium alloy is preferably greater than 70 MPa·m 1 / 2 , more preferably 75~90 MPa·m 1 / 2 , preferably 80~90 MPa·m 1 / 2 , the most preferred is 83~85 MPa·m 1 / 2 .
[0031] The titanium alloy provided by the present invention has a relatively high molybdenum equivalent of 12.12%, and about 2% of Nb and about 1% of Fe are added at the same time. The comprehensive performance ensures that the alloy has relatively high strength, plasticity and toughness.
[0032] The invention provides a method for treating a high-strength and toughness titanium alloy. The composition of the titanium alloy forging includes, by mass, 5.8% to 6.2% Al, 3.8% to 4.2% Mo, 6.8% to 7.2% V, 1.5% to 2.5% Nb, 0.8% to 1.5% Fe, C≤0.05%, O≤0.13%, N≤0.05%, H≤0.015%, and a Ti balance. The heat treatment comprises the following steps: heating the titanium alloy forging to a phase transition temperature + (10 to 30)°C in a stepwise manner for a first heat preservation, then cooling to 670°C to 700°C for a second heat preservation, then transferring to an environment of 400°C to 450°C, heating to 520°C to 610°C for a third heat preservation, and obtaining a high-strength and toughness titanium alloy.
[0033] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.
[0034] In the present invention, the composition of the titanium alloy forging includes, by mass: Al 5.8%~6.2%; Mo 3.8%~4.2%; V 6.8%~7.2%; Nb 1.5%~2.5%; Fe 0.8%~1.5%; C≤0.05%; O≤0.13%; N≤0.05%; H≤0.015%; Ti balance.
[0035] According to the present invention, the Al content in the titanium alloy forging is preferably 5.9% to 6.2%, more preferably 5.9% to 6.11%, and even more preferably 5.98% to 6.11%.
[0036] According to the present invention, the content of Mo in the titanium alloy forging is preferably 3.9% to 4.2%, more preferably 3.95% to 4.2%, and even more preferably 3.99% to 4.18%.
[0037] According to the present invention, the V content in the titanium alloy forging is preferably 6.85% to 7.2%, more preferably 6.85% to 7.15%, and even more preferably 6.88% to 7.12%.
[0038] According to the present invention, the Nb content in the titanium alloy forging is preferably 1.7% to 2.5%, more preferably 1.7% to 2.2%, further preferably 1.9% to 2.2%, and most preferably 1.98% to 2.1%.
[0039] According to the present invention, the content of Fe in the titanium alloy forging is preferably 0.8% to 1.3%, more preferably 0.9% to 1.25%, and even more preferably 0.95% to 1.25%.
[0040] According to the present invention, the C content in the titanium alloy forging is preferably less than or equal to 0.04%, more preferably less than or equal to 0.03%, further preferably less than or equal to 0.02%, and most preferably less than or equal to 0.01%.
[0041] According to the present invention, the content of O in the titanium alloy forging is preferably less than or equal to 0.12%, more preferably less than or equal to 0.1%, and even more preferably less than or equal to 0.08%.
[0042] According to the present invention, the N content in the titanium alloy forging is preferably less than or equal to 0.03%, more preferably less than or equal to 0.02%, further preferably less than or equal to 0.01%, and most preferably less than or equal to 0.008%.
[0043] According to the present invention, the H content in the titanium alloy forging is preferably less than or equal to 0.012%, more preferably less than or equal to 0.01%, further preferably less than or equal to 0.008%, and most preferably less than or equal to 0.005%.
[0044] In the present invention, the titanium alloy forging is obtained by forging a titanium alloy ingot through a two-phase zone forging process in which the ingot is opened and reforged by a process combining repeated upsetting and drawing according to the "high-low-high" method above and below the phase transformation point, and the deformation amount per fire at the phase transformation point is controlled between 45% and 55%, and the deformation amount per fire below the phase transformation point is controlled between 35% and 45%.
[0045] The titanium alloy forging is heated stepwise to the phase transition temperature + (10-30) °C for the first heat preservation; the stepwise heating preferably includes a first stage heating, a second stage heating and a third stage heating; the first stage is preferably heated to 450-550 °C, more preferably to 480-520 °C, more preferably to 490-510 °C, and most preferably to 500 °C; after the first stage heating, it is preferably kept warm for 10-40 min, more preferably for 20-40 min, more preferably for 25-35 min, and most preferably for 30 min; the second stage is preferably heated to 800-830 °C, more preferably for 800-820 °C, more preferably for 805-815 °C, and most preferably for 810 °C; after the second stage heating, it is preferably kept warm for 10-40 min, more preferably for 20-40 min, and more preferably for 25-35 min. min, most preferably 30 min; in the third stage, the temperature is raised to the phase transition temperature + (10-30) °C; the temperature of the first insulation is preferably the phase transition temperature + (10-20) °C, more preferably the phase transition temperature + (10-15) °C; the time of the first insulation is preferably 1-2 h, more preferably 1-1.5 h, and more preferably 1 h.
[0046] After the first insulation is completed, the second insulation is carried out by cooling to 670°C~700°C; the cooling is preferably furnace cooling; the temperature of the second insulation is preferably 670°C~690°C, more preferably 670°C~680°C; the time of the second insulation is preferably 1~4 h, more preferably 2~4 h, more preferably 2.5~3.5 h, and most preferably 3 h.
[0047] After the second insulation, the mixture is transferred to an environment of 400°C~450°C, and the temperature is raised to 520°C~610°C for the third insulation to obtain a high-strength and toughness titanium alloy; the transfer time is preferably not more than 90 s, more preferably not more than 80 s, more preferably 50~80 s, more preferably 60~80 s, more preferably 65~80 s, more preferably 70~75 s, and most preferably 72~75 s; the temperature of the third insulation is preferably 520°C~600°C, more preferably 520°C~580°C, and more preferably 530°C~550°C; the time of the third insulation is preferably 3~5 h, more preferably 4~5 h, and more preferably 5 h; after the third insulation, it is preferably cooled to obtain a high-strength and toughness titanium alloy; the cooling method is a method well known to those skilled in the art, and there is no special limitation. In the present invention, air cooling is preferred.
[0048] The titanium alloy provided by the present invention has both a high aluminum equivalent and a high molybdenum equivalent. At the same time, Nb and Fe can significantly refine the grain size of the titanium alloy, and the addition of Nb can greatly improve the plasticity and toughness of the alloy, so that the alloy has higher strength, plasticity and toughness. At the same time, a specific strengthening and toughening heat treatment process is adopted according to the characteristics of the alloy. The titanium alloy forging is heated above the phase transformation point and then furnace-cooled to a certain temperature to obtain a lamellar structure of a certain thickness, and then quickly converted to a lower temperature. In the process, finer α phases are precipitated, and then more secondary α phases are precipitated through aging, so that the comprehensive performance of strength, plasticity and toughness of the titanium alloy is improved to a new level.
[0049] In order to further illustrate the present invention, a high-strength and toughness titanium alloy and a heat treatment method thereof provided by the present invention are described in detail below in conjunction with embodiments.
[0050] The raw materials used in the following examples are all commercially available.
[0051] The titanium alloy forging described in the embodiment is obtained by forging a titanium alloy ingot through a process combining repeated upsetting and drawing by a "high-low-high" method above and below the phase transformation point, wherein the deformation amount per fire at the phase transformation point is controlled between 45% and 55%, and the deformation amount per fire below the phase transformation point is controlled between 35% and 45%, and the forging is obtained through two-phase zone forging.
[0052] Example 1
[0053] The φ230 mm ingot was prepared by three vacuum consumable melting processes. The composition of the ingot is shown in Table 1. β It is 870℃.
[0054] Table 1 Chemical composition analysis results of the upper, middle and lower alloys
[0055]
[0056] The ingot was opened at high temperature and forged several times at temperatures above and below the phase transition point. Finally, the forging with a cross-sectional thickness of 80 mm was completed in the two-phase region. The forging placed on the tray was heated to 500°C with the furnace, kept warm for 0.5 h, then heated to 810°C, kept warm for 0.5 h, and then heated to 10°C above the phase transition point, that is, 880°C. After keeping warm for 1 h, the forging was furnace cooled to 680°C and kept warm for 3 h. The forging was then quickly transferred to a furnace temperature of 430°C, the transfer time was 72 s, the furnace temperature was raised to 530°C, kept warm for 5 h, and air cooled. Samples were taken from the forgings to measure the properties, as shown in Table 2.
[0057] Table 2 Properties of forgings with a section thickness of 80 mm
[0058]
[0059] Example 2
[0060] The φ600 mm ingot was prepared by three vacuum consumable melting processes. The ingot composition is shown in Table 3. β It is 867℃.
[0061] Table 3 Chemical composition analysis results of the upper, middle and lower alloys
[0062]
[0063] The ingot was opened at high temperature and forged several times at temperatures above and below the phase transformation point. Finally, the forging with a cross-sectional thickness of 180 mm was completed in the two-phase region. The forging placed on the tray was heated to 500°C with the furnace, kept warm for 0.5 h, then heated to 810°C, kept warm for 0.5 h, and then heated to 15°C above the phase transformation point, that is, 882°C. After keeping warm for 1 h, the forging was furnace cooled to 670°C and kept warm for 3 h. The forging was then quickly transferred to a furnace temperature of 400°C for 75 s, the furnace temperature was raised to 550°C, kept warm for 5 h, and air-cooled. The properties of the samples taken on the forgings are shown in Table 4.
[0064] Table 4 Properties of forgings with a section thickness of 180 mm
[0065]
[0066] It can be seen that by adopting the technology of the present invention, the forging strength is greater than 1200 MPa, the elongation is more than 8%, and the fracture toughness is greater than 70 MPa·m 1 / 2 , and there is a certain amount of surplus. When the forging specifications are expanded, the strength, plasticity and toughness of the forgings are matched by adjusting the converter and aging temperature. Compared with the prior art, even for large-section thickness forgings, the forging performance obtained by the technical solution of the present invention can meet the design indicators.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A heat treatment method for high-strength and toughness titanium alloy, characterized in that: The following steps are involved: The titanium alloy forging is heated in stages to the phase transition temperature + (10-30)°C for the first heat preservation, then cooled to 670-700°C for the second heat preservation, then transferred to an environment of 400-450°C, heated to 520-610°C for the third heat preservation, and a high-strength and toughness titanium alloy is obtained; The composition of the titanium alloy forging includes, by mass: Al 5.8%-6.2%; Mo 3.8%-4.2%; V 6.8%-7.2%; Nb 1.5%-2.5%; Fe 0.8%-1.5%; C≤0.05%; O≤0.13%; N≤0.05%; H≤0.015%; Ti balance; The staged heating includes first stage heating, second stage heating and third stage heating; the first stage heating to 450°C~550°C; the first stage heating is followed by heat preservation for 10~40 min; the second stage heating to 800°C~830°C; the second stage heating is followed by heat preservation for 10~40 min; the third stage heating to phase change temperature + (10~30)°C; The first insulation time is 1 to 2 hours; the second insulation time is 1 to 4 hours; the third insulation time is 3 to 5 hours; The transfer time does not exceed 90 s.
2. The heat treatment method according to claim 1, characterized in that The staged heating includes first stage heating, second stage heating and third stage heating; the first stage heating is carried out to 480°C~520°C; the first stage heating is followed by heat preservation for 20~40 min; the second stage heating is carried out to 800°C~820°C; the second stage heating is followed by heat preservation for 20~40 min; the third stage heating is carried out to the phase change temperature + (10~30)°C.
3. The heat treatment method according to claim 1, characterized in that The staged heating includes first stage heating, second stage heating and third stage heating; the first stage is heated to 500°C; the first stage is heated and kept warm for 30 minutes; the second stage is heated to 810°C; the second stage is heated and kept warm for 30 minutes; the third stage is heated to phase change temperature + (10~30)°C.
4. The heat treatment method according to claim 1, characterized in that: The first insulation is carried out by raising the temperature in stages to the phase change temperature + (10~15)℃.
5. The heat treatment method according to claim 1, characterized in that: The titanium alloy forging is obtained by repeatedly upsetting and stretching a titanium alloy ingot through a process combining "high-low-high" method above and below the phase transformation point, and then blanking and reforging the ingot, controlling the deformation amount per fire at the phase transformation point to be between 45% and 55%, and the deformation amount per fire below the phase transformation point to be between 35% and 45%, and then reforging in two phases.
Citation Information
Patent Citations
Low-cost high-strength high-toughness Ti alloy and preparation method thereof
CN105779817A
Heat treatment process of titanium alloy
CN110273118A
Cold rolling method for TC27 titanium alloy pipe
CN111940538A